Mucosal microbiota characterization in gastric cancer identifies immune-activated–related transcripts relevant gastric microbiome signatures - Qian, Chengjia; Hui, Jiang; Peng, Ziyao; Sun, Xiaoyan; Zhang, Jiali (Frontiers in Immunology, 2024)
Tumor microenvironment (TME) immune cells and gastric mucosal microbiome constitute two vital elements of tumor tissue. Increasing evidence has elucidated their clinicopathological significance in predicting outcomes and therapeutic efficacy.However, comprehensive characterization of immune cell-associated microbiome signatures in the TME is still in the early stages of development. Here, we characterized the gastric mucosa microbiome and its associations with immune-activated related transcripts (IATs) in 170 GC tumor tissues and matched non-tumor tissues using 16s rRNA gene sequencing and quantitative reverse transcription-PCR. Microbial diversity and richness were significantly higher in GC tumor tissues than in non-tumor tissues.Differences in microbial composition between the groups were evident, with Firmicutes,